31 Days Before Your CCNA Routing and Switching Exam : a Day-By-Day Review Guide for the ICND2 (200-101) Certification Exam, Third Edition - Johnson, Allan (Cisco Press, 2014)
31 Days Before Your CCNA Routing and Switching Exam offers you a personable and practical way to understand the certification process, commit to taking the 200-101 Interconnecting Cisco Networking Devices Part 2 (ICND2) certification exam, and finish your preparation using a variety of Primary and Supplemental study resources. The ICND2 is the second exam associated with the CCNA Routing and Switching certification. This exam tests your knowledge and skills required to successfully install, operate, and troubleshoot a small- to medium-size enterprise branch network. Sign up for the ICND2 exam and use the book's day-by-day guide and checklist to organize, prepare, and review. Each day in this guide breaks down an exam topic into a manageable bit of information to review using short summaries. A Study Resources section provides you with a quick reference for locating more in-depth treatment of a day's topics within the Primary and Supplemental resources. The features of the book empower you to fit exam preparation into a busy schedule: Visual calendar summarizing each day's study topic Checklist providing advice for preparation activities leading up to the exam Description of the 200-101 ICND2 exam organization and sign up process Strategies from the author to be mentally, organizationally, and physically prepared for exam day Conversational tone, which makes your study time more enjoyable Primary Resources: Cisco CCNA ICND2 200-101 Official Cert Guide ISBN-13: 978-1-58714-373-1 Interconnecting Cisco Network Devices, Part 2 (ICND2) Foundation Learning Guide, Fourth Edition ISBN: 978-1-58714-377-9 Scaling Networks Companion Guide ISBN: 978-1-58713-328-2 Scaling Networks Lab Manual ISBN: 978-1-58713-325-1 Connecting Networks Companion Guide ISBN: 978-1-58713-332-9 Connecting Networks Lab Manual ISBN: 978-1-58713-331-2 Supplemental Resources: CCNA Routing and Switching Practice and Study Guide ISBN: 978-1-58713-344-2 CCNA Routing and Switching Portable Command Guide Third Edition ISBN: 978-1-58720-430-2 Cisco CCNA Routing and Switching 200-120 Network Simulator ISBN: 978-0-7897-5088-4.